Levels of serum hyaluronic acid, TNF-? and IL-8 in patients with nonalcoholic steatohepatitis - Bahcecioglu, IH; Yalniz, M; Ataseven, H; Ilhan, N; Ozercan, IH; Seckin, D; Şahin, Kazım (H G E Update Medical Publishing S A, 2005)
Background/Aims: Nonalcoholic steatohepatitis (NASH) is a common cause of liver disease that comprises a wide spectrum of liver damage, ranging from simple steatosis to steatohepatitis. The aim of this study is to investigate serum hyaluronic acid (HA), TNF-alpha, IL-8 levels in patients with non-alcoholic steatohepatitis and to assess their potential value as a noninvasive marker for the severity of histopathology. Methodology: Twenty-eight patients with biopsyproven NASH, 14 patients with cirrhosis and 15 healthy controls were studied. Histopathological findings were graded and staged. HA, IL-8, TNF-levels were determined using by ELISA test Results: Serum HA levels in patients with NASH were significantly higher than in the healthy control group (P < 0.05). However, the levels in patients with cirrhosis were markedly higher than in patients with NASH and healthy controls (P < 0.001). Serum TNF alpha levels were significantly higher in patients with NASH and cirrhosis than in healthy controls (P < 0.05). Serum IL-8 levels in patients with NASH (P < 0.001) and cirrhosis (P < 0.05) were significantly higher than in the healthy control group. There was no correlation between serum HA and IL-8, TNF-alpha, ALT and AST levels. Serum HA level in patients with NASH was 187.26 +/- 139.21 and 143.49 +/- 93.14 in stage in stage 2-3 and in stage 0-1, respectively, but the difference was not significant (P > 0.05). Conclusions: In conclusion, serum HA, IL-8 and TNF-a levels increased in patients with NASH. Their relation with the severity of histopathology is not significant. Serum HA levels may be a useful marker to monitor the conversion from fibrosis to cirrhosis. Further studies are needed on this topic.
Keywords: nonalcoholic steatohepatitis; histopathology; hyaluronic acid; interleukin-8; TNF-alpha